A FUNCTIONAL STUDY OF SMART CITY UDAIPUR - Dr. Shrishti Raj Singh Chundawat, Samuel Francis (Chelonian Research Foundation, 2022)
The presented research paper is based on the data of functional aspects of Smart City Udaipur.About 31% of India's current population lives in cities and they contribute 63% to the GDP (Census 2011). It is expected that by the year 2030, 40% of India's population will live in urban areas and its contribution to India's GDP will be 75%. This requires comprehensive development of physical, institutional, social and economic infrastructure. All these are important in improving the quality of life and attracting people and investment, establishing a virtuous cycle of development and progress. The development of smart city is a step in this direction.Smart Cities Mission is an innovative and new initiative by the Government of India to enable local development and improve the quality of life through better outcomes for citizens with the help of technology and to accelerate economic growth.